Evidence of a fixed internal gene constellation in influenza A viruses isolated from wild birds in Argentina (2006–2016) - Rimondi, Agustina; Gonzalez Reiche, Ana Silvia; Olivera, Valeria Soledad; Decarre, Julieta; Castresana, Gabriel Julián; Romano, Marcelo; Nelson, Martha I.; van Bakel, Harm; Pereda, Ariel Julian; Ferreri, Lucas; Geiger, Ginger; Perez, Daniel Roberto (Springer Nature, 2019)
Wild aquatic birds are the major reservoir of influenza A virus. Cloacal swabs and feces samples (n = 6595) were collected from 62 bird species in Argentina from 2006 to 2016 and screened for influenza A virus. Full genome sequencing of 15 influenza isolates from 6 waterfowl species revealed subtypes combinations that were previously described in South America (H1N1, H4N2, H4N6 (n = 3), H5N3, H6N2 (n = 4), and H10N7 (n = 2)), and new ones not previously identified in the region (H4N8, H7N7 and H7N9). Notably, the internal gene segments of all 15 Argentine isolates belonged to the South American lineage, showing a divergent evolution of these viruses in the Southern Hemisphere. Time-scaled phylogenies indicated that South American gene segments diverged between ~ 30 and ~ 140 years ago from the most closely related influenza lineages, which include the avian North American (PB1, HA, NA, MP, and NS-B) and Eurasian lineage (PB2), and the equine H3N8 lineage (PA, NP, and NS-A). Phylogenetic analyses of the hemagglutinin and neuraminidase gene segments of the H4, H6, and N8 subtypes revealed recent introductions and reassortment between viruses from the Northern and Southern Hemispheres in the Americas. Remarkably and despite evidence of recent hemagglutinin and neuraminidase subtype introductions, the phylogenetic composition of internal gene constellation of these influenza A viruses has remained unchanged. Considering the extended time and the number of sampled species of the current study, and the paucity of previously available data, our results contribute to a better understanding of the ecology and evolution of influenza virus in South America.